Plant secretome proteomics - Alexandersson, Erik; Ashfaq, Ali; Resjö, Svante; Andreasson, Erik (Frontiers in Plant Science, 2013)
The plant secretome refers to the set of proteins secreted out of the plant cell into the surrounding extra-cellular space commonly referred to as the apoplast. Secreted proteins maintain cell structure and acts in signaling and are crucial for stress responses where they can interact with pathogen effectors and control the extra-cellular environment. Typically, secreted proteins contain an N-terminal signal peptide and are directed through the ER/Golgi pathway. However, in plants many proteins found in the secretome lack such a signature and might follow alternative ways of secretion. This review covers techniques to isolate plant secretomes and how to identify and quantify their constituent proteins. Furthermore, bioinformatical tools to predict secretion signals and define the putative secretome are presented. Findings from proteomic studies and important protein families of plant secretomes, such as proteases and hydrolases, are highlighted.